Royalists and Royalism during the English Civil Wars - McElligott, Jason (Cambridge University Press, 2013)
This volume evolved from an international conference entitled Royalists and Royalism: Politics, Religion, and Culture, 1640–60 that we jointly organized at Clare College, Cambridge, in July 2004. This conference brought together more than seventy scholars and students from four continents and a variety of disciplines, all of whom shared a common interest in mid-seventeenth-century British royalism. The conference proved extraordinarily lively and stimulating, and we hope that something of that atmosphere will be evident in this collection. More than thirty papers were presented at the conference, spanning the period from the late 1630s to the early 1660s, but in the interests of focus and coherence we have decided to concentrate this collection on the period from about 1638 through to the execution of Charles I. We plan in the near future to edit a related collection entitled Royalists and Royalism during the Interregnum.